Generating charged pharmaceutical aerosols intended to improve targeted drug delivery in ventilated infants. (October 2015) - Holbrook, Landon; Hindle, Michael; Longest, P. Worth
Abstract: The delivery of pharmaceutical aerosols to infants receiving mechanical ventilation is extremely challenging due to small diameter flow passages, low tidal volumes, and frequent exhalation of the aerosol. The use of small charged particles is proposed as a novel method to prevent deposition in ventilator components and foster deposition in the lower infant airways. The objective of this study was to compare the performance of multiple new devices for generating small charged particles that are expected to maximize respiratory drug delivery in ventilated infants. Criteria used to select a leading device included production of a charged aerosol with a mass median aerodynamic diameter (MMAD)≤approximately 1.8 µm; low device depositional loss of the aerosol (<20%); particle charge in the range of the Rayleigh limit/100; and high drug output with low performance variability. Proposed new devices were a wick electrospray (WES) system with accelerated cross-flow air; a condensational vapor (CV) system with a charged solution and strong field gradient; and a low flow-induction charger (LF-IC) designed to operate with a modified commercial mesh nebulizer. Based on infant ventilation conditions, flow rates through the devices were in a range of 2–5 L/min and the devices were assessed in terms of depositional drug loss and emitted drug mass; droplet size distribution (DSD) using a Mini-MOUDI; and DSD and net charge with a modified ELPI. Considering the WES, primary limitations were (i) low and variable aerosol production rates and (ii) high device depositional losses. The CV device produced a high quality aerosol with a MMAD of 0.14 µm and a drug delivery rate of 25 µg/min. However, the device was excluded because it failed to produce a charged aerosol. In contrast, the LF-IC produced a 1.6 µm aerosol with high net charge, low device depositional loss (<15% based on recovery), and low variability. In the ELPI size fraction bin nearest the MMAD, the LF-IC produced >100 elementary charges per particle, which was an order of magnitude increase compared to the case of zero charging voltage. In conclusion, the LF-IC was selected as a leading system that is expected to improve aerosol delivery efficiency in ventilated infants through the use of small charged particles. Graphical abstract: Highlights: Small charged particles are proposed to improve pharmaceutical aerosol delivery for ventilated infants. Three new devices are developed to generate an aerosol which is appropriately sized and charged with low device losses. Droplet size distribution and net number of charges per particle are quantified using a Mini-MOUDI impactor at 2 LPM and an electrical low pressure impactor at 30 LPM. The low flow-induction charger device is found to be superior to wick electrospray and condensational vapor devices.